Evaluation of Knowledge, Attitudes, and Practices towards Vaccination among Patients with Spina Bifida in Ukraine - O.R. Boyarchuk; M.V. Koshmaniuk; R.O. Kovalenko (Сучасна педіатрія: Україна)
Patients with spina bifida (SB) face an increased risk of infection due to frequent exposure to medical procedures and visits to healthcare centers, including rehabilitation centers. Infection can lead to complications in kidneys and urinary bladder, disrupt rehabilitation efforts, and reduce the quality of life.